Come in uno specchio: populismo e governamentalità neoliberale - Bazzicalupo, Laura (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
The aim of the essay is to problematize the seemingly obvious dichotomy: liberalism - populism. A double bond holds today the two poles, both involved in the decline of the representative logic. An immanentism broadly aesthetic (at the same time, spectacular and immediately sensitive ) prevails; forms of life and power presume to manifest themselves and act without mediation. Moreover, even the conceptual couple populism/ neoliberalism, which presents itself as emphatically oppositional: hyper - political v/s depoliticization, reveals a paradoxical mirroring. We must rethink the populism of the twenty-first century beyond the traditional categories in which it was framed and we have to bring it back to the neoliberal context from which it emerges.